UNIVERSITAS NAHDLATUL ULAMA SUMATERA UTARA CARING FOR AGAINST COVID-19 - SITI NURLANI harahap; Nurbaity Situmorang; Saiful Amir; Juhardi Sembiring; Rahmat Suryanto Pirngadi (Mejuajua: Jurnal Pengabdian pada Masyarakat, 2021)
The community service aims to provide education and protection to the public regarding the dangers of corona virus which has an impact on health; distributing masks to the public, with the aim that mask users are protected from the corona virus; distributing hand sanitizers to the public, to kill bacteria and viruses on palms of the hands after activities outside the home. This community service activity is in the form of distributing hand sanitizer and masks carried out by lecturers at the Nahdlatul Ulama University of North Sumatera as a form of concern for the academic community for the community around the campus. Community service activities were carried out in village of Klambir V, Hamparan Perak District, Deli Serdang Regency. The method of implementing community service is carried out in 3 stages, namely the preparation stage, the implementation stage and the reporting stage. At the preparatory stage, all documents and products such as hand sanitizers and masks are needed to be distributed to the village community. The implementation stage is carried out by providing masks and hand sanitizers as well as educating the public on the importance of wearing masks and washing hands to prevent the spread of COVID-19. The last stage is the reporting stage, namely compiling the final report on community service activities. The results of this activity were 100 hand sanitizers and 5 dozen masks that were prepared and distributed to the public. There are still many people in the village of Klambir V who don’t care about COVID-19, which is marked by the fact that there are still many people who don’t wear masks and wash their hands with hand sanitizer. There are still many people who don’t know about the dangers of spreading COVID-19, so many still ignore the use of masks and hand sanitizer.